On the accuracy of unit-cell parameters in protein crystallography - Dauter, Zbigniew; Wlodawer, Alexander (Acta crystallographica. Section D, Biological crystallography., 2015)
The availability in the Protein Data Bank (PDB) of a number of structures that are presented in space group P1 but in reality possess higher symmetry allowed the accuracy and precision of the unit‐cell parameters of the crystals of macromolecules to be evaluated. In addition, diffraction images from crystals of several proteins, previously collected as part of in‐house projects, were processed independently with three popular software packages. An analysis of the results, augmented by published serial crystallography data, suggests that the apparent precision of the presentation of unit‐cell parameters in the PDB to three decimal points is not justified, since these parameters are subject to errors of not less than 0.2%. It was also noticed that processing data including full crystallographic symmetry does not lead to deterioration of the refinement parameters; thus, it is not beneficial to treat the crystals as belonging to space group P1 when higher symmetry can be seen.